The application of participatory action research to enhance the health care of the wood-carving community - Susanha Yimyam (2018)
© 2018 Nova Science Publishers, Inc. The Khun-Kong community is famous for its woodcarving production, which contributes significantly to the local economy. However, the work conditions and environment may be harmful and detrimental to the workers' health. This developmental research study, 'Enhancing the Health of the Wood-Carving Community,' used community collaboration to engage with various sectors and groups. Action research is considered one of the most important strategies in confronting health problems and promoting community health. The purpose of this study was to build the self-care capacity among woodcarving workers and their community. The study was divided into two phases: a community and health impact assessment phase; and an implementation phase. Both qualitative and quantitative methods were used in Phase One (community and health impact assessment) to investigate the work conditions and the environments that may impact the health of wood-carving workers and their community. Community-based participatory research was used in Phase Two (community implementation phase) to develop a network of woodcarving workers to promote self-care, to enhance the capability for self-care among peer leaders of wood-carving workers, as well as to develop a self-care guidebook and media tools for a health promotion campaign. This chapter focuses on Phase Two to draw linkages between the principles, approaches and applications of community-based participatory action research through this case study on health promotion among woodcarving workers. Participatory learning was used for peer leader training. Community participation aided the development a self-care network for a health promotion campaign as well as a self-care guidebook and media materials. The self-care network consisted of the research team, a community committee, and trained peer leaders. Quantitative data were analyzed using frequency, percentage and a t-test, whereas qualitative data were analyzed using content analysis. During Phase Two one guidebook and three types of media instruments, namely posters, VCD, and radio spots, were developed. These materials were examined by a group of workers for appropriateness for both content and presentation and were found to be satisfactory. After receiving training, peer leaders' knowledge and awareness of work-related health problems and preventive self-care increased significantly. Their skills and confidence in risk assessment and self-care instruction also improved. The self-care network identified new ways of thinking, problem solving, and sustainable self-care. Self-reliance was perceived as an important aspect of health care. Finally, workers' health status, perception of health risk and health behaviors also improved. In the community, skills in problem identification and problem solving were learned. Although this project was successful in increasing health awareness of the workers and the community, the long-term impact and sustainability of networking and activities need to be examined. Furthermore, co-operation with other relevant institutions or professions are suggested to produce and use the guidebook and media materials with other woodcarving workers to improve work conditions and the environment.